Structures and antifouling properties of self-assembled zwitterionic peptide monolayers : effects of peptide charge distributions and divalent cations - Li, Chuanxi (2020)
Zwitterionic peptides are great candidates as antifouling coating materials in many biomedical applications. We investigated the structure and antifouling properties of surface-tethered zwitterionic peptide monolayers with different peptide chain lengths and charge distributions using a combination of surface plasma resonance, atomic force microscopy, and all atomistic molecular dynamics (MD) simulation techniques. Our results demonstrate that zwitterionic peptides with more zwitterionic lysine (K) and glutamic acid (E) repeating units exhibit better antifouling performance. The block charge distributions of the positive and negative charges in the peptides (having multiple positive charges next to the same amount of negative charges), although affecting the structure of the peptide molecules, do not significantly change the antifouling properties of the peptide monolayers in the solutions containing monovalent ions. However, divalent cations, Ca2+ and Mg2+, in solution can significantly alter the structure and lower the antifouling performance of the zwitterionic peptide monolayers, especially with the sequences of block charges. All atomistic MD simulations quantitatively reveal that the divalent cations in solution lead to more interchain electrostatic cross-links between peptide chains, especially for peptides with block charges, which causes dehydration of the zwitterionic peptides and diminishes their antifouling performances.